2021
DOI: 10.3389/fmicb.2021.709746
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Simultaneous Air Revitalization and Thermal Control in a Crewed Habitat With Temperate Chlorella vulgaris and Eurythermic Antarctic Chlorophyta

Abstract: Including a multifunctional, bioregenerative algal photobioreactor for simultaneous air revitalization and thermal control may aid in carbon loop closure for long-duration surface habitats. However, using water-based algal media as a cabin heat sink may expose the contained culture to a dynamic, low temperature environment. Including psychrotolerant microalgae, native to these temperature regimes, in the photobioreactor may contribute to system stability. This paper assesses the impact of a cycled temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Algal photobioreactors can remove carbon dioxide (CO 2 ), liberate O 2 , remove or alter waste and produce edible biomass ( Matula and Nabity, 2019 ; Fahrion et al, 2021 ). These photobioreactors can withstand the dynamic temperature environment experienced within the ISS thermal control loops ( Matula and Nabity, 2021 ; Matula et al, 2021 ). Preliminary spaceflight studies using algae for ECLSS observed thriving cultures ( Helisch et al, 2020 ; Poughon et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Algal photobioreactors can remove carbon dioxide (CO 2 ), liberate O 2 , remove or alter waste and produce edible biomass ( Matula and Nabity, 2019 ; Fahrion et al, 2021 ). These photobioreactors can withstand the dynamic temperature environment experienced within the ISS thermal control loops ( Matula and Nabity, 2021 ; Matula et al, 2021 ). Preliminary spaceflight studies using algae for ECLSS observed thriving cultures ( Helisch et al, 2020 ; Poughon et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%